PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU DI MASA PANDEMI COVID 19 - Junaidi; Irianto (Manajemen Pendidikan Program Doktor, 2021)
Teacher performance plays an important role in improving the quality of the learning process in an effort to improve the quality of education, especially at the Yabis Bontang educational institution. To achieve optimal learning, teacher work motivation should be high to be able to bring up better teacher performance, so that it can produce quality students and can continue school to a higher level. The research was conducted to examine and find out how much influence teacher work motivation on teacher performance in schools in the Yabis Education Institute, from kindergarten, elementary, junior high and high school units. The method used in this research is ex post facto. To obtain the desired data in the field, this study used a questionnaire compiled using several indicators. The data needed in this study are data on teacher work motivation (X), and teacher performance (Y). Based on the results of data processing and analysis, the following conclusions were obtained; 1)There is a positive influence between work motivation on teacher performance at the Yabis Al-ikhlas Bontang Education Foundation during the Covid 19 pandemic. and 2) Work motivation contributes 44% to teacher performance at the Yabis Bontang Foundation.